Dramatizing Care: An Ethnodrama Into Syrian Refugee Women’s Healthcare Challenges and Coping in Ontario, Canada - Areej Al-Hamad (17770842) (2024)
The complex healthcare struggles faced by Syrian refugee women in Ontario, Canada necessitate innovative methodologies that transcend traditional research dissemination to accurately reflect their diverse lived experiences. Ethnodrama emerges as a potent tool in this context, addressing the noticeable gap in engaging wider audiences—including the refugee women themselves—in the research process through dynamic and impactful knowledge mobilization. This study investigates the healthcare challenges and coping strategies of Syrian refugee women using ethnodrama, explores their potential to facilitate knowledge transfer, empower women, and ultimately impact refugee health policy and practice. As part of a broader critical ethnography project involving 25 Syrian refugee women, this research integrates critical ethnography with intersectionality to delve into the participants’ interactions with the Ontario healthcare system. The data collected were transformed into dramatic scripts, which were then created by the research team in a simulated hospital environment to maintain the confidentiality and anonymity of the study participants. The process entailed iterative script development, filming, and revisions, ensuring that the portrayal was both accurate and resonant, effectively engaging the audience. The study identified three key themes: navigating and coping with healthcare hurdles, barriers to timely specialist care and cultural dissonance in healthcare. The use of ethnodrama not only enhanced the understanding of these issues but also demonstrated its significant potential in empowering refugee women and influencing public policy. By presenting complex social issues in an engaging and comprehensible manner, ethnodrama has proven to be an effective tool for social change, enhancing policy engagement and providing refugee women with a valuable platform to voice their experiences. This approach not only contributes to the fields of qualitative research and public policy but also underscores the transformative power of integrating artistic modalities with traditional research methods to enact social change and empower marginalized communities. Other Information Published in: International Journal of Qualitative Methods License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1177/16094069241293963